2021
DOI: 10.1016/j.jaac.2020.01.015
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Systematic Review and Meta-regression Analysis: Mental Disorders Among Adolescents in Juvenile Detention and Correctional Facilities

Abstract: Objective: To synthesize evidence on the prevalence of mental disorders in adolescents in juvenile detention and correctional facilities and examine sources of heterogeneity between studies. Method: Electronic databases and relevant reference lists were searched to identify surveys published from January 1966 to October 2019 that reported on the prevalence of mental disorders in unselected populations of detained adolescents. Data on the prevalence of a range of mental disorders (psychotic illnesses, major dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
68
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 82 publications
(400 reference statements)
9
68
2
4
Order By: Relevance
“…However, results varied across individual studies and indicated low to high heterogeneity between effect size estimates, mainly due to methodological differences between studies (i.e., setting of care, time period of prevalence, and study design). Due to various moderator variables, our metaanalysis found comparable levels of heterogeneity to those in previous meta-analyses of both child welfare and juvenile justice samples [3,4]. The elevated rates of mental disorders among adults previously in out-of-home care may be explained by the use of samples in the stage of young adulthood (18-25 years) in eight studies [63,65,67,69,70,72,76,77], compared with the highest mean age of 72 years in the study sample of Fernandez et al [78].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, results varied across individual studies and indicated low to high heterogeneity between effect size estimates, mainly due to methodological differences between studies (i.e., setting of care, time period of prevalence, and study design). Due to various moderator variables, our metaanalysis found comparable levels of heterogeneity to those in previous meta-analyses of both child welfare and juvenile justice samples [3,4]. The elevated rates of mental disorders among adults previously in out-of-home care may be explained by the use of samples in the stage of young adulthood (18-25 years) in eight studies [63,65,67,69,70,72,76,77], compared with the highest mean age of 72 years in the study sample of Fernandez et al [78].…”
Section: Discussionsupporting
confidence: 62%
“…Millions of children and adolescents worldwide are placed in out-of-home care, with rates ranging from approximately 0.5-1% between countries [1,2]. The prevalence of mental disorders is high in these children and adolescents [3,4], as they face various challenges related to mental disorders in the transition period from leaving care to adulthood (e.g., homelessness, adult mental disorders, or unemployment; [5][6][7]). To date, the extent of the association between placement in childhood out-of-home care and the occurrence of adult mental disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the clinical profiles ruled out two key malingering strategies (Vilariño et al, 2013;Rogers, 2018): indiscriminate grouping of symptoms (no reported harm in all of the disorders; in fact, hypochondriasis, depression, psychasthenia, schizophrenia, hypomania, and social introversion report normality) and symptom severity (participants reported no severe disorder, T < 90). In short, the systematic tendency to malinger was ruled out in CPOs, i.e., a diagnostic criterion for CD and a differential diagnosis for PTSD in forensic setting (American Psychiatric Association, 2000, a diagnosis with significant rates [61.7% (95% CI 55.4-67.9%) of CD and 8.6% (95% CI 6.4-10.7%) of PTSD] among juvenile offenders (Beaudry et al, 2021). Likewise, systematic defensiveness (defensiveness may consist in denial of symptoms and/or the adoption of desirable characteristicssocial desirability-to mask an unfavorable image; Arce et al, 2015;Rogers, 2018) was ruled out in CPOs: L, K, and the F-K index ruled out the suspicion of defensiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, CPOs experience more symptoms on the basic clinical dimensions than the normative population, but only report clinical deterioration in psychopathic deviation (unreliable, egocentric, and irresponsible; unable to learn from experience and to plan ahead; problems with family members and authority; anger toward others; and problematic interpersonal relations in large interactions and under stress); and moderate deterioration in hysteria (naive, self-centered, denying any problem, exhibitionist, extroverted, and superficial) and paranoia (highly sensitive to criticism and to personalize the actions of others toward themselves). Furthermore, CPOs report more clinical maladjustment than other juvenile justice samples, which is characterized by psychological problems (Baum et al, 2009;Marcos et al, 2020;Beaudry et al, 2021). Hence, the population of CPOs are a clinical population experiencing more deterioration than other samples of juvenile justice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation